Population Trends of Gulls and Arctic Terns Nesting in the Belcher Islands, Nunavut - Gilchrist, H. Grant; Robertson, Gregory J. (ARCTIC, 1999)
Little information exists on the population trends of gulls and terns nesting in the Arctic. In 1997, we surveyed the number of glaucous gull (Larus hyperboreus), herring gull (Larus argentatus), and arctic tern (Sterna paradisaea) nests on the Belcher Islands (56°00'-57°30'N, 79°30'-80°00'W). We compared our results with the mean number of nests per island counted in the Belcher Islands in the late 1980s using the same survey methods. The mean number of gull nests per island had declined in all five archipelagos surveyed, and the decline was significant in three regions. The number of arctic tern nests had also declined in all three regions where they were originally present, although this decline was significant in only one region. The causes of these apparent declines are unknown. Adult mortality or emigration of gulls from the area may have occurred in response to changes in polynya formation during recent winters, which restricted access to marine food sources. Reproductive success of gulls may also be low in response to the recent 75% decline in common eiders nesting in the Belcher Islands. Eider eggs and ducklings are an important food source for gulls during the breeding season. The decline of nesting arctic terns may reflect either winter mortality of tern populations caused by unknown factors or emigration out of the Belcher Islands in response to regional egging and disturbance by local residents. Il existe peu de renseignements sur les tendances dans les changements de population des mouettes et sternes qui nichent dans l'Arctique. En 1997, on a établi un relevé des nids du goéland bourgmestre (Larus hyperboreus), du goéland argenté (Larus argentatus) et de la sterne arctique (Sterna paradisaea) dans les îles Belcher (56° 00' - 57° 30' de latit. N., 79° 30'- 80° 00' de longit. O.). Nous avons comparé nos résultats avec le nombre moyen de nids par île comptés dans les îles Belcher à la fin des années 1980, en employant les mêmes méthodes de relevés. Le nombre moyen de nids de goélands par île a ...